Učinkovitost robotizirane vadbe zgornjih udov pri osebah z okvaro vratnega dela hrbtenjače - Kafel, Tibor (Rehabilitacija (Ljubljana), 2022)
Background: Spinal cord injury impacts all life aspects, physical dysfunction being the most prominent. Early rehabilitation is crucial, part of which is occupational therapy. The main goal of occupational therapy in people with cervical spinal cord injury is participation in everyday life and productive life style. An addition to conventional occupational therapy may also be robot-assisted therapy of the upper limbs, which shows promising efficiency in improving upper limb functions. Methods: A randomised control trial with fourteen participants was conducted, seven in the experimental and seven in the control group. Along the standard occupational therapy intervention, the experimental group was provided ten therapies of robot-assisted therapy and the control group received an additional hour of occupational therapy. The outcome measures used were aligned with recommendations for use in people with spinal cord injury. Results: Participants of the experimental group have statistically significantly increased their left hand grip strength, sensibility as well as in participation and satisfaction assessment (p<0.05). The control group had no statistically significant improvements of functional tests. Between-group comparison of progress showed statistically significant differences in occupational assessment, but not in functional assessments. Conclusion: This study confirmed the effectiveness of robot-assisted therapy in people with cervical spinal cord injury for improving body functions as well as participation in everyday occupations. Robot-assisted therapy is a valuable addition to conventional occupational therapy for improving body functions.
Keywords: Cervical Vertebrae; delovna terapija; occupational therapy; okvara hrbtenjače; rehabilitacija; rehabilitation; robot assisted therapy; Robotics; robotsko podprta terapija; spinal cord injury; Upper Extremity; upper limb; zgornji ud